Corporate citizenship in South African business education - R. Hamann; L. Van Duin; C. Appels; E. Taylor; E. Akor (South African Journal of Business Management, 2006)
This paper seeks to enhance our understanding of the extent and manner in which corporate citizenship and related topics are taught to business students in South Africa. It argues that there are increasingly prominent drivers for integrating these topics in business education, but we know little about how South African business schools are responding. The methodology relies on a survey of business schools' websites, as well as two survey questionnaires, one of which was aimed at MBA coordinators, while the other targeted a range of "MBA stakeholders" consisting of recent MBA graduates and representatives from business, government, and civil society. The findings suggest that, though there are some proactive business schools, South African MBA programmes are generally still dominated by conventional notions of business success. Furthermore, there are important contradictions between the perceptions of MBA coordinators, on the one hand, and those of the MBA stakeholders, with the latter generally demanding more rigorous treatment of corporate citizenship Issues. The overarching conclusion is that a more committed engagement of and by South African business schools is required on the need for integrating corporate citizenship in business education.
Keywords: 650